L’héritier du diadème chez les Antigonides - Le Bohec-bouhet, Sylvie (Gerión. Revista de Historia Antigua, 2006)
In the Antigonid dynasty, the heir of the throne was the eldest son of the king and the designation of the new king was happening without difficulties. Apart from the case of Demetrios, the younger son of Philip V, the Macedonian royal house did not suffer dynastic murders. The events around Philip’s succession show that the king could appoint an other heir if he wanted to. As so far we know, there is no word to designate the “crown prince” who, probably, was introduced by his father to the Firsts of the Macedonians and to the Assembly. The king prepared his heir to his future task by giving him a good education and associating him to various political activities. In some cases, for diplomatic reasons, the king could choose a wife for his heir. In many occasions, when the father received honours from individuals or from cities, the royal heir was associated.